2010
DOI: 10.1007/s11136-009-9575-y
|View full text |Cite
|
Sign up to set email alerts
|

Validity of information obtained from a method for estimating cancer costs from the perspective of patients and caregivers

Abstract: Evidence to date supports the validity of estimates obtained using this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…However, it is not surprising. Collecting these costs is not straightforward as instruments to collect them are not available [28]. Therefore, opportunities to collect OOP costs from participants of clinical trials of survivorship interventions or from larger populations of survivors are missed.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not surprising. Collecting these costs is not straightforward as instruments to collect them are not available [28]. Therefore, opportunities to collect OOP costs from participants of clinical trials of survivorship interventions or from larger populations of survivors are missed.…”
Section: Discussionmentioning
confidence: 99%
“…And then we missed out on that $1000 threshold thing that they got and we were back to square one when the next year started and we never got on where the medication decreased. NHL_RegRural_48yrs_M reliable and validated instruments are not available to collect data on OOP costs [3,30]. Indeed, the lack of instruments is seen as partly contributing, through lost opportunity, to the lack of work completed in the area.…”
Section: Limitationsmentioning
confidence: 99%
“…There may also be a trade-off between specifying the costs that researchers expect patients will think important, in order to trigger their memory, versus allowing free space for patients to express other costs they feel are important but overlooked by researchers [18]. The complexity of the question is also relevant in terms of the extent to which the patient must mentally sum numerous and diverse costs in order to arrive at a total cost [10,13].…”
Section: Measuring Oop Costs In Prospective Researchmentioning
confidence: 99%
“…Yet the availability of instruments to examine OOP costs in cancer patients is limited (for breast cancer, one US review identified just 3 studies which had examined them) [7] and few have been validated in terms of showing they accurately capture the costs they were designed to measure [10].…”
mentioning
confidence: 99%